EmpoWord A Student-Centered Anthology & Handbook for College Writers - Abrams, Shane (Open textbook library., 2018)
EmpoWord is a reader and rhetoric that champions the possibilities of student writing. The textbook uses actual student writing to exemplify effective writing strategies, celebrating dedicated college writing students to encourage and instruct their successors: the students in your class. Through both creative and traditional activities, readers are encouraged to explore a variety of rhetorical situations to become more critical agents of reading, writing, speaking, and listening in all facets of their lives. Straightforward and readable instruction sections introduce key vocabulary, concepts, and strategies. Three culminating assignments (Descriptive Personal Narrative; Text-Wrestling Analysis; Persuasive Research Essay) give students a chance to show their learning while also practicing rhetorical awareness techniques for future writing situations.